Intestinal alkaline phosphatase activity as a molecular marker of enterotoxicity induced by single dose of 5-fluorouracil and protective role of orally administered glutamine - Bajin-Katić Katica; Stankov Karmen; Đolai Matilda; Kovačević Zoran (Archive of Oncology, 2006)
Background. One of the critical limitations for the administration of the chemotherapy is the toxicity affecting normal tissue. The main target organs for 5-fluorouracil (5-FU) toxicity in humans and experimental animals are the gastrointestinal tract, bone marrow, and skin. The cytotoxic effects of antimetabolite chemotherapy are based on their role as substrates for the same transport processes and enzymes involved in anabolism and catabolism as the natural substrates. The main goal of our study was to analyze the dose-dependent antiproliferative effects of 5-FU on intestinal mucosa, enterotoxic potential of 5-FU in experimental animals and to test possible protective role of glutamine. Methods. In our study, we used Sprague Dawley rats. The control group of rats included 50 animals, while the groups where either 5-fluorouracil (5-FU) alone or 5-FU and glutamine were administered included 200 animals. All experimental animals were further stratified according to the experimental model (25 animals in each of 8 experimental subgroups of animals). The 5-FU was administered by intraperitoneal application in single dose of 0, 100, 200, 300, and 400 mg of 5-FU per kg of body weight. Water solution of 1% glutamine was prepared daily and administered orally, in volume of 200 ml, for 7 days continuously, after the 7th day of 5-FU administration. Experimental animals were sacrificed 7 days after the administration of 5-FU. The isolation of enterocytes was performed according to the method of Kralovansky et al. In cell homogenate obtained by described method, we determined the protein content using the Biuret method and the DNA content using the Burton reagent. The activities of enzymes alkaline phosphatase (ALP), glutathione S-transferase (GST), glutathione reductase (GR), and glutathione peroxidase (GPX) were determined by kinetic method. All paraffin samples of the small intestine were stained by haematoxiline and eosine(HE method). All the experiments were done in duplicate and analyzed by standard statistical methods. All the experiments were done in duplicate and analyzed by standard statistical methods. Results: Our results of enterotoxicity induced by intraperitonealy administered 5-FU showed statistically significant decrease of DNA content in small intestine samples of experimental animals, decrease in activity of intestinal alkaline phosphatase enzyme and the increase in glutathione-dependent enzymes. The glutamine supplementation reduced 5-FU intestinal toxicity. Conclusion: Intestinal alkaline phosphatase is a good marker of the dose-dependent enterotoxicity induced by 5-fluorouracil.